Pengaruh Media Tanam pada Berbagai Konsentrasi Nutrisi terhadap Pertumbuhan dan Hasil Seledri dengan Sistem Tanam Hidroponik NFT - Kun Rawan Sari; Jamzuri Hadie; Chatimatun Nisa (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
Celery is a commercial plant that should be cultivated. Nutrient Film Technique Hydroponic cultivation systems is one of the technologies that can be applied in a narrow area, but research of the planting medium and the concentration of nutrients in hydroponiccultivation system for celery plants are rare. This study aimed to analyze the influence interaction planting medium and nutrient concentrations on the growth and yield of celery. The design of this study used split plot design. The main plot were the concentration of nutrients (N): 1200 ppm (n1), 1300 ppm (n2), and 1400 ppm (n3). Subplot were the planting mediums (M): rockwool as control (m0), sawdust (m1), husk fuel (m2), and rice straw (m3). There were twelve combinations, with three replicates. The results showed that treatment interaction was not significant effect on growth and yield, but a single treatment of plant media rockwool and nutrient concentration of 1300 ppm able to increase the growth and yield of celery.